2006
DOI: 10.1007/s10661-006-0360-x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Atmospheric Deposition with Coniferous Canopies in Estonia

Abstract: Throughfall and open field bulk precipitation were measured at three coniferous sites during 1995-2002 in the framework of ICP Integrated Monitoring and at five coniferous sites during 1996-2002 in the framework of ICP Forests (Level II). The coniferous canopies acted as a sink for nitrate and ammonium and as a source for base cations: Ca(2+), Mg(2+) and K(+). The estimated share of SO(4)-S dry deposition from total deposition was 1.5-4 times higher for dormant period compared to growing period. During the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…They attributed this difference to canopy uptake dynamics. Canopy uptake of NO 3 − and NH 4 + as reported in literature suggests that total inorganic N deposition will be underestimated (Johnson and Lindberg 1992;Jin et al 2006;Pajuste et al 2006). In the IFS data, net dry throughfall deposition of NO 3 − was estimated at 752 eq ha −1…”
Section: Discussionmentioning
confidence: 85%
“…They attributed this difference to canopy uptake dynamics. Canopy uptake of NO 3 − and NH 4 + as reported in literature suggests that total inorganic N deposition will be underestimated (Johnson and Lindberg 1992;Jin et al 2006;Pajuste et al 2006). In the IFS data, net dry throughfall deposition of NO 3 − was estimated at 752 eq ha −1…”
Section: Discussionmentioning
confidence: 85%
“…Throughfall deposition fluxes of Ca, Mg, K, S-SO 4 , N-NO 3 and N-NH 4 in the mountain spruce stands of different stand density and bulk deposition fluxes on the open area were measured at the study site Bílý , 1993, -1996, (Marchetti et al 2002 3 Saarejärve locality, 1995(Pajuste et al 2006 15.7 and 11.6, 4.2 and 3.0, 19.2 and 12.7, 22.5 and 16.4, 8.9 and 7.4, 7.7 and 6.6 kg/ha, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The share of this process in the tree stand under analysis was estimated at 74.1% of the potassium deposition in the throughfall. Pajuste et al (2006) obtained values ranging from 40-73% for pine and spruce stands in Estonia. Similar values were quoted by Herrmann et al (2006) for two pine stands situated in north-west Germany (44-71%).…”
Section: Discussionmentioning
confidence: 96%
“…Pajuste et al (2006) provide values ranging from 4.8-5.6 for pine and spruce stands in Estonia. Terauda et al (2007) obtained values ranging from 5.4-5.8 for pine stands in Lithuania in 2004, while Hermmann et al (2006 reported the pH of the throughfall of 5.6 in north-west Germany.…”
Section: Discussionmentioning
confidence: 99%